Hybridization of common reed in North America? The answer is blowing in the wind - Meyerson, L A; Lambertini, C; McCormick, M K; Whigham, D F (AoB PLANTS, 2012)
BACKGROUND AND AIMS: We review evidence for hybridization of Phragmites australis in North America and the implications for the persistence of native P. australis ssp. americanus populations in North America. We also highlight the need for an updated classification system, which takes P. australis intraspecific variation and hybridization into account. METHODOLOGY: We reviewed available published, in press and in preparation literature to assess the likelihood of hybridization and interbreeding in genotypes of P. australis present in North America. PRINCIPAL RESULTS: Experimental results demonstrate that hybridization among introduced and native haplotypes is possible within the genus Phragmites, yet evidence that hybridization has occurred naturally is only starting to emerge. The lag in identifying hybridization in Phragmites in North America may be related to under-sampling in some parts of North America and to a lack of molecular tools that provide the capability to recognize hybrids. CONCLUSIONS: Our understanding of the gene flow within and between species in the genus Phragmites is moving at a fast pace, especially on the east and Gulf coasts of North America. More attention should also be focused on the Great Lakes region, the southwestern and the west coast of the USA, where sympatry has created opportunities for hybridization. Where hybridizations have been detected, there are currently no published data on how hybridization affects plant vigour, morphology, invasiveness or conservation of the genetic integrity of the North American native subspecies. We conclude that the detection of more hybridization is highly likely and that there is a need to develop new markers for the different Phragmites species and lineages to fill current knowledge gaps. Finally, we suggest that the classification system for P. australis should be updated and published to help clarify the nomenclature.